2018
DOI: 10.1080/01480545.2018.1510416
|View full text |Cite
|
Sign up to set email alerts
|

In vivo genotoxicity assessment of sunset yellow and sodium benzoate in female rats

Abstract: The use of additives in different food products is growing up. It has attracted the attention towards the relation between the mutagenic potential of human diseases and food additives. Sunset yellow (SY) and sodium benzoate (NaB) are used as colorant and food additives worldwide. In the present study, genotoxic effects of different combinations of SY and NaB were assessed in vivo in female rats. Different combinations of SY and NaB were dissolved in water and administered daily to six animals groups for 12 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 39 publications
0
7
0
2
Order By: Relevance
“…These data confirmed the previously reported in vitro and in vivo clastogenic effects of SY. According to Ali et al [25], a mixture of SY and sodium benzoate led to structural abnormalities in rat chromosomes such as fragmentation, ring chromosome, centric fusion breakage, and chromatid breakage. In mice, SY has been reported to have genotoxic effects based on the increased frequency of CAs in bone marrow and germ cells [3].…”
Section: Discussionmentioning
confidence: 99%
“…These data confirmed the previously reported in vitro and in vivo clastogenic effects of SY. According to Ali et al [25], a mixture of SY and sodium benzoate led to structural abnormalities in rat chromosomes such as fragmentation, ring chromosome, centric fusion breakage, and chromatid breakage. In mice, SY has been reported to have genotoxic effects based on the increased frequency of CAs in bone marrow and germ cells [3].…”
Section: Discussionmentioning
confidence: 99%
“…The activation is accomplished by acetyltransferases, which are widely distributed in animals [8,40] . Ali et al [41] also found that oral administration of mixture of SY (as coloring agent) and sodium benzoate (as a food additives) in different concentrations to female rats for 12 weeks caused DNA damage in their hepatocytes, which confirmed by different types of comet assay. In addition, Hassan [8] reported that rats orally administrated two concentration of Tz (7.5 and 15 mg/kg body weight/day) for 7 weeks caused DNA damage in liver cells that increased by increasing the concentration.…”
Section: Discussionmentioning
confidence: 92%
“…Another example is the dye Amaranth, which was shown to induce DNA damage in the colon epithelium of mice [33][34][35], while Brilliant Black BN has shown genotoxicity in human lymphocytes based on in vitro experiments [36]. Sunset Yellow FCF can cause DNA damage and has shown to have toxic effects on the reproductive and neurobehavioral system of tested rodents and chick embryos [37,38]. Tartrazine was shown to bind to albumin, induce neurotoxicity, impair mental functions, and promote various reactions such as angioedema, nasal congestion, itchy skin, and hives [23].…”
Section: Impacts Of Azo Dyes On Human Health and The Environmentmentioning
confidence: 99%